Transformative Climates and Accountable Governance - Edmondson, Beth.; Levy, Stuart; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'Transformative and Accountable Climate Governance describes the paradigmatic influences and frameworks within which transformations and transitions in light of a warming earth will occur. The book thereby pursues a multi-disciplinary angle and offers an impressive interdisciplinary approach with truly international outlook. In its entirety, the book is therefore of direct relevance for academia, practitioners and public policy specialists around the globe.' - Julia M. Puaschunder, Prize Fellow at the Inter-University Consortium of New York, USA This book explores the real-world consequences changing ideas and strategies have on effective climate governance. Its main focus is on why accountability matters - both for transformations and transitions in international climate change governance and how international support for environmentally responsible actions, and extending shared accountabilities, might strengthen climate governance globally. A main point of discussion is if and how better understanding of accountabilities and transformations in ecosystems dynamics, the capacities of organisms to adapt, migrate or otherwise respond to environmental or climatic changes, can improve climate governance mechanisms. Bringing together a diverse set of considerations from various fields of study, chapters examine responses to environmental transformations that occur during periods of climatic crisis, such as species depletion, industrialisation, de-industrialisation or urbanisation. Throughout, this book aims to further readers understanding of if or how accountable climate governance can reduce the risks of global political disorder and widespread conflict in the 21st century, arising from environmental transformations of depleted forests, re-routed waterways, coastlines impacted by sea level rises, changed rainfall patterns and industrial practices. Beth Edmondson is a senior lecturer in the School of Arts at Federation University Australia. Her research focuses on international responses to global climate change, the possibilities for order in the international political system, the nature of sovereignty and the scope of international law in constructing governmental capacities. Stuart Levy is a senior lecturer in the School of Education at Federation University Australia. His interests in international relations include the nature and evolution of state sovereignty and the politics of global climate change. .
Chapter 1: Introduction: Transformative Climates and Accountable Governance; Beth Edmondson & Stuart Levy -- Section One: Chapter 2: The Limits of States and Changing Regulatory Frameworks; Beth Edmondson & Stuart Levy -- Chapter 3: Order and Accountability in Governing Transforming Environments; Beth Edmondson & Stuart Levy -- Chapter 4: Climate Governance for Nation States in the Anthropocene - an agenda for transformation in Australia; Josephine Mummery & Jane Mummery -- Chapter 5: The Empire Strikes Back: Fossil Fuel Companies, Investor-State Dispute Settlement, International Trade, and Accountable Governance; Matthew Rimmer -- Chapter 6: The public's perception of international climate leadership: Insights from the European Union; Jale Tosun, Mile Micic & Nicole Schmidt -- Section Two: Chapter 7: Selected studies in Economic & Environmental Accountabilities; Beth Edmondson & Stuart Levy -- Chapter 8: Allocating the Burdens of Climate Action: Consumption-basedCarbon Accounting and the Polluter-pays Principle; Ross Mittiga -- Chapter 9: Comparison of climate change, human and non-human migration governance; Martina Grecequet, Jessica Hellmann, Jack DeWaard & Yudi Li -- Chapter 10: Representing whose access and allocation interests? Stakeholder perceptions and interests representation in climate governance; Timothy Cadman, Tek Maraseni, Hugh Breakey & Hawn Ok Ma -- Chapter 11: Constraining supply: the moral case for limiting fossil fuel exports; Jeremy Moss -- Chapter 12: Personal carbon trading and individual mitigation accountability ; Steven Vanderheiden -- Chapter 13: Conclusion: Where to next? Accountable Governance and Transformative Climates; Beth Edmondson & Stuart Levy.
Keywords: Environment; Physical geography; Climatology; Human geography; Environmental Sciences; Physical Geography; Climate Sciences; Human Geography